(untitled) (City: History, Culture, Society, 2022)
The famous historic Old Town of Elbląg in northern Poland was comprehensively destroyed in the Second World War, neglected for several decades in the post-war period, and rebuilt from scratch in a postmodern style from 1979 onwards. The new, flamboyant, historically inspired buildings were promoted by the local Head Conservationist Maria Lubocka-Hoffmann and financed by the fledgling market economy. Developing against the background of an international trend towards old town regeneration, these buildings grew from different roots than postmodernism in the West. They derived from an expanded concept of historic conservation and the goal to reconcile contradictory desires. These included a contested past in a town that had been German until 1945, a longing for local identity and visible historicity despite historical ruptures, and the establishment of traditional planning principles such as small scale and mixed use in a modern environment.